Behavior Management of Students Based on Parental Involvement - Ach Rizquha; Moh Rofiki (Yayasan Avicenna, 2023)
This study aims to determine how student behavior management is based on parental involvement and what factors hinder its implementation. The qualitative approach used in this research is multi-site. The research locations were MI Azzainiyah II and MTs Azzainiyah II. Data collection techniques included participant observation, in-depth interviews, and documentation studies. Informants in obtaining data consisted of the principal, vice principal for student affairs, teachers, and student guardians. The data analysis used consists of single-case data analysis and cross-case data analysis. The results showed that involvement-based learner behavior management is implemented to assist schools in carrying out educational tasks and enriching the learning experience gained by students. Parents' participation in student behavior management is to supervise or control their children's learning time and learning methods; monitor the development of their children's academic abilities; monitor the development of their personalities, which include attitudes, morals, and behavior; and ask about the activities their children do while at school. Meanwhile, the factors that hinder student behavior management include health factors, intelligence factors, attention factors, interest factors, and talent factors.